Technology for Social Change in school contexts: a new landscape for K-12 educational technology research - Antoniou, Chrystalla G.; Ioannou, Andri (My University, 2018)
Based on the assumption that technology can positively impact our society and help address larger societal problems, and given the fact that technology is a central component of children’s growth, the current study places its research focus on technology-enhanced social change in K-12 education. The study summarizes literature that has been published within the past decade (2006–2017) which has employed technology as a tool for achieving social change via working with K-12 school students. Despite the limited number of manuscripts that emerged to meet these criteria, the reviewed studies revealed evidence suggesting that the intentional use of technology within school contexts can become a means for fostering social change by achieving student behavioral and/or attitudinal shifts. The summary of research calls for more work towards specific directions: targeting school-aged students, designing interventions grounded in theoretical and design foundations, documenting the long-lasting impact of results, addressing technology mediated perspective-taking and addressing how technology-mediation functions.
Keywords: Research summary; Review; Technology-enhanced learning; Social change; Social outcomes; Perspective-taking; K-12